2002
DOI: 10.1002/nur.10056
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial outcomes of vaginal and cesarean births in Taiwanese primiparas

Abstract: The purpose of this study was to examine differences in psychosocial outcomes between primiparas experiencing vaginal deliveries and primiparas experiencing cesarean deliveries. One hundred and ninety-four vaginal delivery primiparas and 81 cesarean delivery primiparas from the Kaohsiung city area in Taiwan were recruited at 6 weeks postpartum to participate in this study. Using two-sample t tests, we found no significant differences in perceived stress, self-esteem, or depression between vaginal and cesarean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
2
11
1
Order By: Relevance
“…In the study of Hollander et al [19] emotional and practical support by the medical team during labor was associated with decreased possibility of PTSD following childbirth and according to Simpson et al [21], low quality of the caregivers interactions during labor was reported as one of the most important risk factors for experiencing traumatic birth. In general, social support has an important role in decreasing stress and other mental problems following childbirth [22]. Similar to the present study, in an Iranian study decreased social support after delivery was associated with PTSD [23].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the study of Hollander et al [19] emotional and practical support by the medical team during labor was associated with decreased possibility of PTSD following childbirth and according to Simpson et al [21], low quality of the caregivers interactions during labor was reported as one of the most important risk factors for experiencing traumatic birth. In general, social support has an important role in decreasing stress and other mental problems following childbirth [22]. Similar to the present study, in an Iranian study decreased social support after delivery was associated with PTSD [23].…”
Section: Discussionsupporting
confidence: 85%
“…Other studies also supported the effect of infant's restlessness and crying and problem in taking care of the infant on developing PTSD following childbirth [6,7]. Other studies have also reported a significant relationship between infant's crying and postpartum depression [22,25]. This is the first prevalence study regarding the PTSD following childbirth based on DSM-V in Iran as a strong point of the present study.…”
Section: Discussionsupporting
confidence: 75%
“…This is in support of earlier findings in Australia [5] and USA [6] which had concluded that women who had CS had worse mood and lowered self-esteem in early post-partum and that operative intervention carries significant psychological risks rendering those who went through CS vulnerable to grief reaction or loss of self-esteem. Our study is however in disagreement with Chen and Wang [7], and Fawcett et al [9] who found no significant difference in perceived stress, self-esteem or depression between mothers with SVD and those who had CS. The pride of women could be a possible explanation of the discrepancies with studies conducted in other countries/settings, hence there may be an associated loss of self-esteem in African mothers who have operative deliveries.…”
Section: Discussioncontrasting
confidence: 70%
“…Local studies conducted in Ilesa, Western Nigeria have demonstrated the high psychiatric morbidity following CSs [3,4]. Although some studies have concluded that compared with women who had spontaneous vaginal delivery (SVD), CS women had worse mood and lowered self-esteem in the early post-partum period [5,6], other studies have found no difference [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The main concerns that women have during childbirth are those of extreme pain and a sense of loss of control [92] , and these issues are best addressed with good communication, allowing women to feel as much in control as possible and offering good pain relief [84] . A study that assessed psychosocial outcomes like stress, self-esteem and depression at 6 weeks postpartum found that there was no difference in these scores after a vaginal delivery, elective CS or emergency CS [16] . More recent studies show that maternal satisfaction from a planned CS is at least as high [119] , if not higher [72] than a planned vaginal delivery and indeed, the only randomised trial that addressed this issue, showed no difference in postpartum depression whether delivery was vaginal or by elective CS [36] .…”
Section: Psychological Experiencementioning
confidence: 98%